Variantangivelser i en dansk produktionsordbog ud fra eksempler med fleksionsangivelser i Retskrivningsordbogen - Bergenholtz, Henning (HERMES - Journal of Language and Communication in Business, 1998)
Looking at articles on language in the newspapers, you will find it striking how many readers are interested in the permissibility of certain expressions. How can we decide if a word or an inflection is allowed? Some people think that the use gives the necessary answers, while others are of the opinion that the customs and especially the language customs are degenerating and therefore cannot serve as decision maker. More than 270 years ago this battle was fought under the watchwords: usus tyrannus and usus imper-ans. This was of course not the first attempt to define the differences between descrip-tive and prescriptive linguistics, and it was indeed not the last one. Despite of that now no really convincing solutions have been given until now. This is due not only to diffe-rent opinions on the relation between the use of the language and its rules, but also to the following factors: (a) the empirical basis of the description, and (b) the aim of the description. In this article it will be shown that purely descriptive information does not help clearly enough by problems on language production, and that extremely prescriptive information helps too little by problems on language reception. In other words, we need prescriptive rules for production and descriptive ones for reception. For this form of prescription which builds on a selection on descriptive data we introduce the expression proscription.